A LANGUAGE ASSESSMENT IN ONLINE LEARNING:CHALLENGES AND EFFECTIVE STRATEGIESFOR ESP CLASSROOMS - Fitria Muji Pratawati; Nur Farah Ukhrowiyah; Mutiatun Nasihah (Universitas Muhammadiyah Kalimantan Timur, 2021)
This study is intended to find out the strategies used to assess the students and some challenges faced by lecturers in ESP classes at UIN Maulana Malik Ibrahim Malang. The researchers were interested in finding the types of assessment and how lecturers conduct assessment during pandemic era. An exploratory sequential mixed methods design was used in this study to answer the research questions. Both quantitative and qualitative design were used to deepen the data. The subjects in this research were English lecturers who taught ESP classes in several majors at UIN Maliki Malang. The results from data collection revealed that the assessment which employed by lecturers was fit with the characteristics of students. The differences of assessment were caused by the students’ dissimilar characteristics and their background. Finally, this study addressed suggestions for English lecturers, stakeholder and future researchers regarding the assessment to run in online class. Assessment must be created and developed well for the students before they join the lesson and the lecturer has to use several strategies to handle in case if one of the assessment tools does not work.